2011
DOI: 10.1097/bcr.0b013e318217f87a
|View full text |Cite
|
Sign up to set email alerts
|

Burn Assault With Paint Thinner Ignition: An Unexpected Burn Injury Caused by Street Children Addicted to Paint Thinner

Abstract: The frequency of assault by burning among all burn patients varies from country to country. Assault by burning, although uncommon, is a serious form of trauma and a significant source of morbidity and mortality. The aim of this retrospective study was to identify the epidemiologic features, current etiological factors, and the mortality of nine patients admitted to our burn unit between January 1999 and January 2009 after unexpected burn assault by paint thinner ignition caused by street children addicted to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We have reported prevalence of paint thinner burn of 7.6% in this study. Kulahci et al [6] investigated demographic features of 9 male patients who were the victims of paint thinner burn and reported that mean %TBSA was as high as 67.7% with mortality rate of 33.3%. Benbrahim et al [7] examined demographic features of 17 patients admitted with paint thinner flame burns.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported prevalence of paint thinner burn of 7.6% in this study. Kulahci et al [6] investigated demographic features of 9 male patients who were the victims of paint thinner burn and reported that mean %TBSA was as high as 67.7% with mortality rate of 33.3%. Benbrahim et al [7] examined demographic features of 17 patients admitted with paint thinner flame burns.…”
Section: Discussionmentioning
confidence: 99%
“…These burn-deformities become a source of lifelong shame, guilt, and regret for the patients. They experience serious image problems that disrupt their social lives, even if they have stabilised emotionally 567. We report our experience in such a specific case in which custom-made planning is required to correct her post-burn breast deformity.…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, in Turkey too, burns comprise a major problem for the health care system and afflicted people and their relatives. Compared to western countries, burns afflict the Turkish population more [1][2].…”
Section: Introductionmentioning
confidence: 99%